2017
DOI: 10.3389/fphar.2017.00109
|View full text |Cite
|
Sign up to set email alerts
|

New Insights toward Colorectal Cancer Chemotherapy Using Natural Bioactive Compounds

Abstract: Combination therapy consists in the simultaneous administration of a conventional chemotherapy drug (or sometimes, a radiotherapy protocol) together with one or more natural bioactives (usually from plant or fungal origin) of small molecular weight. This combination of anticancer drugs may be applied to cell cultures of tumor cells, or to an animal model for a cancer type (or its xenograft), or to a clinical trial in patients. In this review, we summarize current knowledge describing diverse synergistic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 184 publications
(215 reference statements)
0
79
0
Order By: Relevance
“…Numerous studies have reported the anticancer effects of herbal medicines or phytochemicals for the treatment of CRC. Herbal medicines may have improved efficacy and safety compared to other regimens as well as the potential to be used as a complementary therapy for advanced colorectal adenocarcinoma and mCRC [10][11][12]. Examples of current clinically used phytochemicals include Catharanthus alkaloids (Vinca rosea) [13] and Camptotheca (happy tree, cancer tree) [14], while others are currently in clinical trials such as curcumin, green tea and soybeans [15].…”
mentioning
confidence: 99%
“…Numerous studies have reported the anticancer effects of herbal medicines or phytochemicals for the treatment of CRC. Herbal medicines may have improved efficacy and safety compared to other regimens as well as the potential to be used as a complementary therapy for advanced colorectal adenocarcinoma and mCRC [10][11][12]. Examples of current clinically used phytochemicals include Catharanthus alkaloids (Vinca rosea) [13] and Camptotheca (happy tree, cancer tree) [14], while others are currently in clinical trials such as curcumin, green tea and soybeans [15].…”
mentioning
confidence: 99%
“…As allicin targets multiple signal transduction pathways, it is also conceivable that this lyophilized garlic extract may prove useful in combination with mechanistically distinct chemotherapeutic agents, such as the ones that we propose. In fact, the use of natural compounds for combinatorial therapy in cancer treatment is a new promising line of research [39][40][41]. Moreover, because of its pharmacological safety, this garlic extract has been proposed to be used alone to prevent cancer and in combination with chemotherapy to treat cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids possess a documented anticancer activity toward a number of cancer cell lines (Redondo‐Blanco, Fernández, Gutiérrez‐del‐Río, Villar, & Lombó, ). Unfortunately, these activities have not always been confirmed in humans (Iriti & Varoni, ).…”
Section: Phytochemicals As Anti‐invasion Antimetastatic and Antiangmentioning
confidence: 99%